Agama dan Teologi Perlawanan Terhadap Korupsi - Amir Mu'allim (Unisia, 2005)
The corruption cases in Indonesia constitute complex problem because they relate to economical affairs, socio-cultural, that of politic. Actually many ways have been conducted  by govemment to solve the corruption but those do not run effectively. In this sense, the problem is how to solve the corruption problems in term of religion doctrine. To solve the corruption problems, of course, it needs reforming understanding of religion., Searching new paradigm of religion based on the ethic of religion ( not only normative/Theological approach), and transform  it in real human life, in particular regarding corruption cases. The religious leaders can play an important role to support govemment to solve corruption problems based on control teaching of religion.